A Conversation Analysis on the Difference of Language Related to Gender - Risa Triassanti; Muthmainnah; Vargheese KJ (Pro-ELLitera, 2024)
There were several aspects analyzed in this research related to the differences done by women and men in their language used in conversation. The aspects were: a) The amount of talk. b) TurnTaking. The data of this study was in form of video conversation and its transcription. There were three participants in this conversation, President Clinton, Founder and CEO of Theranos Elizabeth Holmes and Executive Chairman of the Alibaba Group Jack Ma. The first finding was about the amount of talk. It was found that Ken talk the most during the conversation, followed by Joanne and the Lenore. This finding broke the stereotype that men talk less than women. The second finding was about turn-taking. There were two kinds of turn-taking system discussed in this research (other-selection and self-selection). It turned out that Joanne had the smallest amount of other selection but had the highest amount of self-selection.